Correlation between bulbar functionality and laryngeal penetration and/or laryngotracheal aspiration on motor neuron disease - Brandão, Bárbara Carolina; Galdino, Alline de Sousa; Lourenção, Luciano Garcia; Trindade, Glaucia Santana; Orate, Magali Aparecida; Silva, Menezes da; Silva da, Roberta Gonçalves [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: Describe and correlate bulbar functionality with laryngeal penetration and/or laryngotracheal aspiration for different food consistencies in Motor Neuron Disease (MND). Methods: Study participants were 18 individuals diagnosed with MND regardless of the type and time of onset of disease. The Amyotrophic Lateral Sclerosis Functional Rating Scale - Revised/BR (ALSFRS-R/BR) was applied, and only the bulbar parameter, which includes speech, salivation and swallowing, was analyzed, with scores raging from 0 (disability) to 12 (normal functionality). Swallowing videofluoroscopy was performed using the Penetration-Aspiration Scale (PAS) described by Rosenbek et al. (1996). The Pearson correlation test was used for data analysis. Results: According to food consistency, the PAS level ranged from 1 to 5 for puree consistency, 1 to 4 for thickened liquid, and 1 to 3 for liquid, and no laryngotracheal aspiration was observed. Negative correlation between bulbar functionality and laryngeal penetration was observed for all food consistencies (pasty: r=-0.487, p=0.041; thickened liquid: r=-0.442, p=0.076; liquid r=0.460, p=0.073), but statistically significant difference was found only for the puree consistency, that is, individuals with poor bulbar functionality presented higher levels of laryngeal penetration. Conclusion: Negative correlation was observed between bulbar functionality and laryngeal penetration in MND. The bulbar parameters of the ALSFRS-R/BR are significant for predicting risk of laryngotracheal aspiration for pasty consistency in MND.
Keywords: Deglutition disorders; Motor neuron disease; Videofluoroscopy